Patches
The patch enhances hydrophilic drug absorption by combining a hydrophilic drug, acrylic polymer, and urea, improving skin permeation while maintaining adhesive strength and reducing residue.
Patent Information
- Application Number
- JP2020206360
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-12-11
AI Technical Summary
Conventional patches exhibit low percutaneous absorption of hydrophilic drugs and deteriorating adhesive properties, particularly due to the skin's barrier function and sebum film, which hinders the permeation of hydrophilic drugs, and adhesive residue issues.
The patch incorporates a hydrophilic drug, an acrylic polymer containing 5% by mass of N-vinyl-2-pyrrolidone, a water-soluble liquid additive, and urea, which enhances transdermal absorption by promoting moisture migration and maintaining adhesive strength through the use of acrylic polymer (A) to retain the additive within the layer.
The solution improves the transdermal absorption of hydrophilic drugs while maintaining excellent adhesive properties, reducing adhesive residue and ensuring effective skin permeation without compromising adhesion.
Smart Images

Figure 0007600661000001 
Figure 0007600661000002
Abstract
Description
[Technical field]
[0001] The present invention provides a patch that reduces the deterioration of adhesiveness and improves the transdermal absorbability of a hydrophilic drug. [Background technology]
[0002] Conventionally, drugs are administered to the human body via the mouth in the form of oral preparations such as tablets, capsules, syrups, etc. However, oral preparations can cause problems such as degradation due to the first-pass effect in the liver, occurrence of gastrointestinal disorders, and occurrence of side effects due to rapid fluctuations in blood concentration.
[0003] Therefore, a method has been proposed in which a drug-containing patch is applied to the skin to administer the drug to the human body through the skin. The patch generally includes a support and an adhesive layer containing an adhesive polymer and a drug. The patch allows the drug to be gradually absorbed through the skin, so that side effects caused by an excessive increase in the drug blood concentration can be reduced. In addition, when an intolerable side effect occurs, the patch can be removed from the skin to immediately stop the transdermal administration of the drug. Furthermore, for patients who have difficulty swallowing drugs, the drug can be easily administered by simply applying the patch.
[0004] Patches are used to administer drugs into the body through the skin. Therefore, patches are required to have excellent adhesion so that they can be reliably attached to the skin without peeling off during use, and can be peeled off after use without leaving any adhesive residue. The adhesive residue refers to the phenomenon in which at least a part of the adhesive layer remains on the skin surface when the patch is peeled off from the skin. If adhesive residue occurs, the skin surface becomes sticky, which may cause discomfort to the patient.
[0005] In addition, the skin has a barrier function, which prevents chemical substances and bacteria from entering the body through the skin. This barrier function is exerted in part by the sebum film that covers the surface of the skin. The sebum film is formed by mixing sweat and lipophilic sebum. Therefore, among drugs, hydrophilic drugs have a problem of being particularly difficult to permeate the skin and having low transdermal absorbability. Therefore, Patent Document 1 discloses an emulsion patch containing a hydrophilic drug and an emulsion adhesive. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2014-210759 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in conventional patches, the transdermal absorbability of hydrophilic drugs remains low, and further improvement is desired.
[0008] Therefore, the present invention provides a patch that reduces the decrease in adhesiveness and improves the transdermal absorbability of a hydrophilic drug. [Means for solving the problem]
[0009] The patch of the present invention comprises a support and an adhesive layer laminated and integrated onto one side of the support, the adhesive layer comprising a hydrophilic drug, an acrylic polymer (A) containing 5% by mass or more of an N-vinyl-2-pyrrolidone component, a water-soluble liquid additive, and urea.
[0010] [Adhesive layer] The patch comprises an adhesive layer laminated integrally on one surface of the backing, the adhesive layer containing a hydrophilic drug, an acrylic polymer (A), a water-soluble liquid additive, and urea.
[0011] (hydrophilic drugs) The adhesive layer contains a hydrophilic drug. In the present invention, the hydrophilic drug means a drug with the highest solubility in water when the solubility of the drug in each solvent is compared using water, ethyl acetate, or toluene as a solvent. The solubility of the drug means the mass (g) of the drug dissolved in 100 g of a saturated solution obtained by dissolving the drug in a solvent at 25°C. The solubility of the drug in water means the maximum solubility of the drug in water having a pH of 2 to 9, which is adjusted using a pH adjuster or buffer as necessary. In the "water having a pH of 2 to 9", the pH of the water means the pH of the water before dissolving the drug. In addition, when measuring the solubility of the drug in water, the pH of the solution in which the drug is dissolved in water may vary with the addition of the drug, but the pH of the saturated solution does not need to be 2 to 9, and may be less than 2 or more than 9. That is, when measuring the solubility of a drug in water, the pH of the water before dissolving the drug should be 2 to 9, and the pH of the saturated solution in which the drug is dissolved may be outside the range of 2 to 9. Examples of pH adjusters that can be used include organic acids such as citric acid, malic acid, fumaric acid, tartaric acid, lactic acid, and succinic acid, and salts thereof; inorganic acids such as phosphoric acid and hydrochloric acid; and inorganic bases such as sodium hydroxide. Examples of buffers that can be used include phosphates such as trisodium phosphate and sodium dihydrogen phosphate.
[0012] Examples of hydrophilic drugs include guanfacine hydrochloride, azelastine hydrochloride, ropinirole hydrochloride, donepezil hydrochloride, and midodrine hydrochloride. Among them, guanfacine hydrochloride, azelastine hydrochloride, ropinirole hydrochloride, and donepezil hydrochloride are preferred. The percutaneous absorbability of these hydrophilic drugs can be particularly improved according to the present invention. The hydrophilic drugs may be used alone or in combination of two or more.
[0013] The content ratio of the hydrophilic drug in the adhesive layer is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, more preferably 2 parts by mass or more, and particularly preferably 5 parts by mass or more, based on 100 parts by mass of the total amount of the hydrophilic drug, the acrylic polymer (A) containing 5% by mass or more of the N-vinyl-2-pyrrolidone component, the water-soluble liquid additive, and the urea. The content ratio of the hydrophilic drug in the adhesive layer is preferably 25 parts by mass or less, more preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and particularly preferably 10 parts by mass or less, based on 100 parts by mass of the total amount of the hydrophilic drug, the acrylic polymer (A) containing 5% by mass or more of the N-vinyl-2-pyrrolidone component, the water-soluble liquid additive, and the urea. When the content ratio of the hydrophilic drug is 0.5 parts by mass or more, a patch capable of administering the hydrophilic drug at the skin permeation amount required for treatment can be provided. When the content of the hydrophilic drug is 25 parts by mass or less, the amount of the hydrophilic drug remaining in the adhesive layer after use of the patch can be reduced.
[0014] (Acrylic polymer (A)) The adhesive layer contains an acrylic polymer (A) containing 5% by mass or more of an N-vinyl-2-pyrrolidone component. This acrylic polymer (A) is preferably used as an acrylic adhesive. The acrylic polymer (A) may be used alone or in combination of two or more kinds. The acrylic polymer (A) containing 5% by mass or more of an N-vinyl-2-pyrrolidone component may be simply referred to as "acrylic polymer (A)".
[0015] In the patch of the present invention, the adhesive layer is made of a combination of an acrylic polymer (A), urea, and a water-soluble liquid additive, which makes it possible to improve the transdermal absorbability of hydrophilic drugs. The mechanism by which such an effect is obtained is not clear, but the following mechanism is considered. The following mechanism is based on the inventors' speculation. Therefore, the present invention is not limited to the following mechanism.
[0016] The water-soluble liquid additive can dissolve at least a part of the urea contained in the adhesive layer. The dissolved urea can easily migrate from the adhesive layer to the skin surface. The urea that has migrated to the skin surface can attract moisture contained in the body to the skin surface, thereby appropriately improving the moisture content on the skin surface. This makes it easier for the hydrophilic drug to permeate the skin, and can improve the transdermal absorbability of the hydrophilic drug. On the other hand, the water-soluble liquid additive has low compatibility with conventional adhesives, and when the water-soluble liquid additive is contained in the adhesive layer, the water-soluble liquid additive may bleed out to the surface of the adhesive layer (bleed out), causing a decrease in the adhesive strength of the adhesive layer and adhesive residue, etc., which may result in a decrease in the adhesiveness of the patch. However, in the present invention, by using an acrylic polymer (A) containing 5% by mass or more of an N-vinyl-2-pyrrolidone component, the water-soluble liquid additive can be reduced from bleed out to the surface of the adhesive layer, and the water-soluble liquid additive can be retained in the adhesive layer, thereby maintaining excellent adhesiveness of the patch. In this manner, in the patch of the present invention, by using a combination of the acrylic polymer (A), urea, and a water-soluble liquid additive, it is possible to provide a patch in which the deterioration of adhesiveness is reduced and the transdermal absorbability of a hydrophilic drug is improved.
[0017] The content of the N-vinyl-2-pyrrolidone component in the acrylic polymer (A) is 5% by mass or more, preferably 7% by mass or more, more preferably 9% by mass or more. The content of the N-vinyl-2-pyrrolidone component in the acrylic polymer (A) is preferably 40% by mass or less, more preferably 30% by mass or less, more preferably 20% by mass or less, and particularly preferably 15% by mass or less. By making the content of the N-vinyl-2-pyrrolidone component 5% by mass or more, the water-soluble liquid additive can be retained in the adhesive layer, and the bleeding out of the water-soluble liquid additive to the surface of the adhesive layer can be reduced. This allows the adhesive layer to maintain excellent adhesive strength, and the decrease in the adhesiveness of the patch can be reduced. On the other hand, by making the content of the N-vinyl-2-pyrrolidone component 40% by mass or less, the cohesive strength of the adhesive layer can be appropriately maintained, and the excellent adhesive strength of the adhesive layer can be maintained.
[0018] The acrylic polymer (A) preferably contains a vinyl monomer component other than the N-vinyl-2-pyrrolidone component. That is, the acrylic polymer (A) preferably contains an N-vinyl-2-pyrrolidone component and a vinyl monomer component other than the N-vinyl-2-pyrrolidone component. The vinyl monomer means a monomer having an ethylenically unsaturated double bond. The vinyl monomer may be used alone or in combination of two or more kinds.
[0019] Examples of vinyl monomers include alkyl (meth)acrylates, vinyl acetate, vinyl chloride, α-olefins, and styrene. Examples of α-olefins include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-nonene, 1-decene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. Among these, alkyl (meth)acrylates are preferred.
[0020] The acrylic polymer (A) preferably contains an alkyl (meth)acrylate component. That is, the acrylic polymer (A) preferably contains an N-vinyl-2-pyrrolidone component and an alkyl (meth)acrylate component. The acrylic polymer (A) is more preferably a copolymer of N-vinyl-2-pyrrolidone and an alkyl (meth)acrylate. The alkyl (meth)acrylate component can impart an appropriate cohesive force to the adhesive layer and improve the adhesiveness of the adhesive layer. Here, (meth)acrylate means acrylate or methacrylate.
[0021] The alkyl group of alkyl (meth)acrylate is -C n H 2n+1 (wherein n is a positive integer.) The alkyl group of the alkyl (meth)acrylate preferably has 1 to 16 carbon atoms, more preferably 1 to 14 carbon atoms, still more preferably 2 to 12 carbon atoms, and particularly preferably 2 to 10 carbon atoms.
[0022] Examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, hexadecyl (meth)acrylate, cyclododecyl (meth)acrylate, and cyclohexyl (meth)acrylate. Among them, ethyl (meth)acrylate, n-octyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred, ethyl (meth)acrylate and n-octyl (meth)acrylate are more preferred, and ethyl acrylate and n-octyl acrylate are more preferred. The alkyl (meth)acrylates may be used alone or in combination of two or more kinds.
[0023] The content of the alkyl (meth)acrylate component in the acrylic polymer (A) is preferably 60% by mass or more, more preferably 65% by mass or more, more preferably 70% by mass or more, and particularly preferably 85% by mass or more. The content of the alkyl (meth)acrylate component in the acrylic polymer (A) is preferably 95% by mass or less, more preferably 93% by mass or less, and particularly preferably 91% by mass or less. By making the content of the alkyl (meth)acrylate component 60% by mass or more, the cohesive strength of the adhesive layer can be set in an appropriate range, and the adhesive strength of the adhesive layer can be improved. By making the content of the alkyl (meth)acrylate component 95% by mass or less, the acrylic polymer (A) can contain a sufficient amount of N-vinyl-2-pyrrolidone component.
[0024] The polymerization method of the acrylic polymer (A) may be carried out by a conventionally known method. For example, the above-mentioned monomer is polymerized in the presence of a polymerization initiator. Specifically, a method is exemplified in which a predetermined amount of monomer, polymerization initiator, and polymerization solvent are supplied to a reactor, and heated at a temperature of 60 to 80°C for 4 to 48 hours to radically polymerize the monomer.
[0025] Examples of the polymerization initiator include azobis-based polymerization initiators such as 2,2'-azobisisobutyronitrile (AIBN), 1,1'-azobis(cyclohexane-1-carbonitrile), and 2,2'-azobis-(2,4'-dimethylvaleronitrile); and peroxide-based polymerization initiators such as benzoyl peroxide (BPO), lauroyl peroxide (LPO), and di-tert-butyl peroxide. Examples of the polymerization solvent include ethyl acetate, cyclohexane, and toluene. Furthermore, the polymerization reaction is preferably carried out under a nitrogen gas atmosphere.
[0026] The content ratio of the acrylic polymer (A) in the adhesive layer is preferably 45 parts by mass or more, more preferably 50 parts by mass or more, and particularly preferably 55 parts by mass or more, based on 100 parts by mass of the total amount of the hydrophilic drug, the acrylic polymer (A) containing 5% by mass or more of an N-vinyl-2-pyrrolidone component, the water-soluble liquid additive, and the urea. The content ratio of the acrylic polymer (A) in the adhesive layer is preferably 90 parts by mass or less, more preferably 85 parts by mass or less, and particularly preferably 80 parts by mass or less, based on 100 parts by mass of the total amount of the hydrophilic drug, the acrylic polymer (A) containing 5% by mass or more of an N-vinyl-2-pyrrolidone component, the water-soluble liquid additive, and the urea. When the content ratio of the acrylic polymer (A) is 45 parts by mass or more, the adhesive strength of the adhesive layer to the skin can be improved. By setting the content ratio of the acrylic polymer (A) to 90 parts by mass or less, the drug and other additives can be added to the adhesive layer in the required amount.
[0027] (Water-soluble liquid additive) The adhesive layer contains a water-soluble liquid additive. The water-soluble liquid additive dissolves at least a part of the urea contained in the adhesive layer, and promotes migration of the dissolved urea to the surface of the adhesive layer. The water-soluble liquid additive is also easily retained in the adhesive layer by the acrylic polymer (A). This allows the adhesive layer to maintain excellent adhesive strength, and reduces the decrease in the adhesiveness of the patch.
[0028] The term "water-soluble" in the context of the water-soluble liquid additive means that the water-soluble liquid additive dissolves in an amount of 10% by mass or more in water having a temperature of 25° C. and a pH of 7. In the context of "water having a pH of 7," the pH of the water refers to the pH of the water before the water-soluble liquid additive is dissolved therein.
[0029] The term "liquid" for water-soluble liquid additives means that the liquid is at 25°C and has a viscosity of 1.01 x 10 5 This means that it is liquid at 1 Pa (1 atm).
[0030] Examples of the water-soluble liquid additive include polyhydric alcohols such as glycerin, propylene glycol, butylene glycol, polyethylene glycol, D-sorbitol, and 1,2,6-hexanetriol. These water-soluble liquid additives can be dissolved in water having a temperature of 25° C. and a pH of 7 at a concentration of 10% by mass or more. Among these, glycerin, propylene glycol, and polyethylene glycol are preferred, glycerin and propylene glycol are more preferred, and glycerin is more preferred. The water-soluble liquid additives may be used alone or in combination of two or more kinds.
[0031] The content ratio of the water-soluble liquid additive in the adhesive layer is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, and particularly preferably 7 parts by mass or more, based on 100 parts by mass of the total amount of the hydrophilic drug, the acrylic polymer (A) containing 5% by mass or more of the N-vinyl-2-pyrrolidone component, the water-soluble liquid additive, and the urea. The content ratio of the water-soluble liquid additive in the adhesive layer is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, more preferably 20 parts by mass or less, and particularly preferably 15 parts by mass or less, based on 100 parts by mass of the total amount of the hydrophilic drug, the acrylic polymer (A) containing 5% by mass or more of the N-vinyl-2-pyrrolidone component, the water-soluble liquid additive, and the urea. When the content ratio of the water-soluble liquid additive is 3 parts by mass or more, at least a part of the urea contained in the adhesive layer can be dissolved, and the migration of the dissolved urea to the surface of the adhesive layer can be promoted. By setting the content ratio of the water-soluble liquid additive to 30 parts by mass or less, it is possible to reduce bleeding out of an excess amount of the water-soluble liquid additive onto the surface of the adhesive layer, thereby enabling the adhesive layer to maintain excellent adhesive strength and reducing the decrease in the adhesiveness of the patch.
[0032] In the adhesive layer, the mass ratio of the water-soluble liquid additive to the hydrophilic drug (mass of water-soluble liquid additive / mass of hydrophilic drug) is preferably 0.1 or more, more preferably 0.2 or more, more preferably 0.5 or more, and particularly preferably 1.0 or more. In the adhesive layer, the mass ratio of the water-soluble liquid additive to the hydrophilic drug (mass of water-soluble liquid additive / mass of hydrophilic drug) is preferably 20 or less, more preferably 10 or less, more preferably 7 or less, and particularly preferably 3 or less. When the mass ratio (mass of water-soluble liquid additive / mass of hydrophilic drug) is 0.1 or more, the transdermal absorbability of the hydrophilic drug can be improved. When the mass ratio (mass of water-soluble liquid additive / mass of hydrophilic drug) is 20 or less, a patch can be provided in which the transdermal absorbability of the hydrophilic drug is improved while reducing the decrease in adhesiveness.
[0033] (urea) The adhesive layer contains urea. Although hydrophilic drugs are difficult to permeate through the skin, even when such hydrophilic drugs are used, the permeation of the hydrophilic drugs through the skin can be promoted by using urea in combination with a water-soluble liquid additive. This makes it possible to provide a patch that is excellent in the percutaneous absorption of hydrophilic drugs.
[0034] In the adhesive layer, it is preferable that at least a part of the urea is contained in a dissolved state. Also, in the adhesive layer, it is preferable that a part of the urea is precipitated in a crystalline state. That is, it is more preferable that the adhesive layer contains urea in a crystalline state.
[0035] In the adhesive layer, urea can be contained in a dissolved state by the water-soluble liquid additive at least in part. When crystalline urea is contained in the adhesive layer, the dissolved urea in the adhesive layer can migrate to the skin surface, and when the concentration of urea in the adhesive layer decreases, the crystalline urea can dissolve and migrate to the skin surface. In particular, the crystalline urea contained in the adhesive layer can gradually migrate to the surface of the adhesive layer, which allows hydrophilic drugs to be continuously permeated through the skin.
[0036] In the adhesive layer, the mass ratio of urea to the hydrophilic drug (mass of urea / mass of hydrophilic drug) is preferably 0.15 or more, more preferably 0.25 or more, and particularly preferably 0.3 or more. In the adhesive layer, the mass ratio of urea to the hydrophilic drug (mass of urea / mass of hydrophilic drug) is preferably 30 or less, more preferably 15 or less, more preferably 10 or less, and particularly preferably 5 or less. When the mass ratio of urea (mass of urea / mass of hydrophilic drug) is 0.15 or more, the transdermal absorbability of the hydrophilic drug can be improved. When the mass ratio of urea (mass of urea / mass of hydrophilic drug) is 30 or less, a patch can be provided that reduces the decrease in adhesiveness and improves the transdermal absorbability of the hydrophilic drug.
[0037] In the adhesive layer, the mass ratio of urea to the water-soluble liquid additive (mass of urea / mass of water-soluble liquid additive) is preferably 0.15 or more, more preferably 0.2 or more, and particularly preferably 0.3 or more. In the adhesive layer, the mass ratio of urea to the water-soluble liquid additive (mass of urea / mass of water-soluble liquid additive) is preferably 6 or less, more preferably 5 or less, and particularly preferably 4 or less. When the mass ratio (mass of urea / mass of water-soluble liquid additive) is 0.15 or more, the transdermal absorbability of hydrophilic drugs can be improved. When the mass ratio (mass of urea / mass of water-soluble liquid additive) is 6 or less, at least a part of the urea can be dissolved by the water-soluble liquid additive, and the migration of the dissolved urea to the surface of the adhesive layer can be promoted.
[0038] The content ratio of urea in the adhesive layer is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and particularly preferably 5 parts by mass or more, based on 100 parts by mass of the total amount of the hydrophilic drug, the acrylic polymer (A) containing 5% by mass or more of the N-vinyl-2-pyrrolidone component, the water-soluble liquid additive, and the urea. The content ratio of urea in the adhesive layer is preferably 35 parts by mass or less, more preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and particularly preferably 20 parts by mass or less, based on 100 parts by mass of the total amount of the hydrophilic drug, the acrylic polymer (A) containing 5% by mass or more of the N-vinyl-2-pyrrolidone component, the water-soluble liquid additive, and the urea. When the content ratio of urea is 1 part by mass or more, the transdermal absorbability of the hydrophilic drug can be improved. When the content ratio of urea is 35 parts by mass or less, a patch having excellent adhesiveness can be provided.
[0039] (Transdermal absorption enhancer) The adhesive layer preferably contains a percutaneous absorption enhancer. By using the percutaneous absorption enhancer, the percutaneous absorbability of the hydrophilic drug can be improved.
[0040] The percutaneous absorption enhancer is preferably water-insoluble. The term "water-insoluble" in the percutaneous absorption enhancer means that the concentration of the percutaneous absorption enhancer that can be dissolved in water having a temperature of 25° C. and a pH of 7 is preferably 1% by mass or less. In the "water having a pH of 7", the pH of the water refers to the pH of the water before the percutaneous absorption enhancer is dissolved.
[0041] Examples of the percutaneous absorption enhancer include fatty acid esters such as isopropyl myristate, decyl oleate, and isopropyl adipate. Among these, isopropyl myristate is preferred. The percutaneous absorption enhancer may be used alone or in combination of two or more kinds.
[0042] The content ratio of the percutaneous absorption enhancer in the adhesive layer is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, based on 100 parts by mass of the acrylic polymer (A) containing 5% by mass or more of the N-vinyl-2-pyrrolidone component. The content ratio of the percutaneous absorption enhancer in the adhesive layer is more preferably 30 parts by mass or less, more preferably 25 parts by mass or less, more preferably 20 parts by mass or less, based on 100 parts by mass of the acrylic polymer (A) containing 5% by mass or more of the N-vinyl-2-pyrrolidone component. When the content ratio of the percutaneous absorption enhancer is 5 parts by mass or more, the percutaneous absorbability of the hydrophilic drug can be improved. When the content ratio of the percutaneous absorption enhancer is 30 parts by mass or less, the cohesive force of the adhesive layer can be appropriately maintained, and the occurrence of adhesive residue can be reduced when the patch is peeled off from the skin after use.
[0043] The adhesive layer may contain other additives such as a tackifier and a filler, provided that the addition of such additives does not affect the skin irritation of the patch.
[0044] (tackifier) The adhesive layer may contain a tackifier. Examples of the tackifier include terpene resin, modified terpene resin, hydrogenated terpene resin, terpene phenol resin, rosin, hydrogenated rosin, rosin ester, petroleum resin, coumarone-indene resin, phenol resin, xylene resin, and alicyclic saturated hydrocarbon resin. The tackifier may be used alone or in combination of two or more. When the adhesive layer contains a tackifier, the content ratio of the tackifier in the adhesive layer is preferably 20 to 80 parts by mass, more preferably 30 to 70 parts by mass, based on 100 parts by mass of the acrylic polymer (A) containing 5% by mass or more of an N-vinyl-2-pyrrolidone component.
[0045] (Filler) The adhesive layer may contain a filler. The filler is used to adjust the shape retention of the adhesive layer. Examples of the filler include inorganic fillers such as light anhydrous silicic acid, titanium oxide, and zinc oxide; organic metal salts such as calcium carbonate and magnesium stearate; cellulose derivatives such as lactose, crystalline cellulose, ethyl cellulose, and low-substituted hydroxypropyl cellulose; and crosslinked polyvinylpyrrolidone. The fillers may be used alone or in combination of two or more. When the adhesive layer contains a filler, the content ratio of the filler in the adhesive layer is preferably 5 parts by mass or less, more preferably 0.1 to 2 parts by mass, based on 100 parts by mass of the acrylic polymer (A) containing 5% by mass or more of an N-vinyl-2-pyrrolidone component.
[0046] The adhesive layer may contain water, but preferably does not substantially contain water. Therefore, it is preferable not to intentionally blend water into the adhesive layer in the manufacturing process of the patch. However, the adhesive layer absorbs water contained in the air during the manufacturing process or storage of the patch, making it difficult to completely remove water from the adhesive layer. Therefore, the water content in the adhesive layer is preferably 1% by mass or less, more preferably 0.5% by mass or less. By making the water content 1% by mass or less, it is possible to reduce the reaction of the hydrophilic drug with water during storage of the patch. If the hydrophilic drug reacts with water, the expected medicinal effect for treatment may not be obtained. In addition, by making the water content 1% by mass or less, the adhesive layer can exert sufficient adhesive force and maintain excellent adhesiveness of the patch.
[0047] The adhesive layer may contain a surfactant, but preferably does not contain a surfactant. Examples of the surfactant include a nonionic surfactant, an anionic surfactant, a cationic surfactant, and an amphoteric surfactant.
[0048] Examples of anionic surfactants include fatty acid soaps, naphthenic acid soaps, long-chain alcohol sulfates, polyoxyethylene alkyl phenyl ether sulfates, fatty acid monoglyceride sulfates, fatty acid monoalkanolamide sulfates, alkali sulfonates, α-sulfofatty acid salts, dialkyl sulfosuccinates, polyoxyethylene octyl phenyl ether sulfonates, alkyl benzene sulfonates, polyoxyethylene alkyl phenol ether phosphates, polyoxyethylene alkyl ether phosphates, and sodium lauryl sulfate.
[0049] Examples of the cationic surfactant include long-chain primary amine salts, alkyl trimethyl ammonium salts, dialkyl dimethyl ammonium salts, alkyl pyridinium salts, polyoxyethylene alkyl amines, and alkyl imidazolines.
[0050] Examples of amphoteric surfactants include N-alkyl β-aminopropionate and N-alkyl β-iminodipropionate.
[0051] Examples of nonionic surfactants include polyglycerol condensed ricinoleate, decaglycerol ester, glycerol fatty acid ester, polyglycerol fatty acid ester, polyoxyethylene glycerol fatty acid ester, sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, polyoxyethylene sorbit fatty acid ester, polyoxyethylene castor oil / hydrogenated castor oil, propylene glycol fatty acid ester, and sucrose fatty acid ester (sucrose stearate, sucrose palmitate, sucrose myristate, sucrose oleate, sucrose laurate, sucrose erucate, and sucrose mixed fatty acid ester).
[0052] The surfactant content in the adhesive layer is preferably 1% by mass or less, more preferably 0.5% by mass or less. By keeping the surfactant content at 1% by mass or less, the adhesive layer can exert sufficient adhesive strength and maintain excellent application properties of the patch.
[0053] The thickness of the adhesive layer is preferably 20 μm or more, more preferably 30 μm or more, and particularly preferably 50 μm or more. The thickness of the adhesive layer is preferably 200 μm or less, more preferably 150 μm or less, and particularly preferably 120 μm or less. When the thickness of the adhesive layer is 20 μm or more, the adhesive layer can contain a necessary amount of drug to obtain a desired medicinal effect. When the thickness of the adhesive layer is 200 μm or less, strong drying conditions are not required during production to reduce the remaining solvent in the adhesive layer, so that the volatilization or decomposition of the drug in the adhesive layer can be suppressed.
[0054] [Support] In the patch of the present invention, an adhesive layer is laminated and integrated on one side of the support. The support is required to have strength to prevent loss of the drug in the adhesive layer and to impart self-retention to the patch. Examples of such supports include resin films, nonwoven fabrics, woven fabrics, knitted fabrics, and aluminum sheets.
[0055] Examples of resins constituting the resin film include cellulose acetate, rayon, polyethylene terephthalate, plasticized vinyl acetate-vinyl chloride copolymer, nylon, ethylene-vinyl acetate copolymer, plasticized polyvinyl chloride, polyurethane, polyethylene, polypropylene, polyvinylidene chloride, etc. Among these, polyethylene terephthalate is preferred because it can prevent loss of the drug from the adhesive layer.
[0056] Examples of materials constituting the nonwoven fabric include polyethylene, polypropylene, ethylene-vinyl acetate copolymer, ethylene-methyl (meth)acrylate copolymer, nylon, polyester, vinylon, SIS copolymer, SEBS copolymer, rayon, cotton, etc., with polyester being preferred. These materials may be used alone or in combination of two or more.
[0057] The support may be a single layer or a laminated sheet in which multiple layers are laminated together, such as a laminated sheet in which a polyethylene terephthalate film is laminated together with a nonwoven fabric or a flexible resin film.
[0058] The thickness of the support is not particularly limited, but is preferably 2 μm or more, and is preferably 200 μm or less, and more preferably 100 μm or less.
[0059] [Release liner] In the patch of the present invention, a release liner may be integrally laminated in a releasable manner on one side of the adhesive layer. The release liner is used to prevent loss of the drug in the adhesive layer and to protect the adhesive layer.
[0060] Examples of the release liner include paper and resin film. Examples of the resin constituting the resin film include polyethylene terephthalate, polyethylene, polypropylene, polyvinyl chloride, polyvinylidene chloride, etc. It is preferable that the surface of the release liner facing the adhesive layer is subjected to a release treatment.
[0061] [Method of manufacturing patch] Examples of methods for producing the patch of the present invention include: (1) a method in which an adhesive layer solution containing a hydrophilic drug, an acrylic polymer (A), a water-soluble liquid additive, urea, and a solvent, and, if necessary, other additives, is applied to one side of a backing, and then dried to laminate an adhesive layer onto one side of the backing, and, if necessary, a release liner is laminated onto the adhesive layer such that the release-treated surface of the release liner faces the adhesive layer; and (2) a method in which the above-mentioned adhesive layer solution is applied to the release-treated surface of a release liner, and then dried to form an adhesive layer on the release liner, and then the backing is laminated onto the adhesive layer.
[0062] The adhesive layer solution is obtained by uniformly stirring the hydrophilic drug, the acrylic polymer (A), the water-soluble liquid additive, urea, and the solvent, and other additives as necessary. Examples of the solvent include toluene, normal hexane, cyclohexane, normal heptane, and ethyl acetate. The solvent may be used alone or in combination of two or more kinds.
[0063] As described above, the patch of the present invention improves the percutaneous absorption of hydrophilic drugs while reducing the decrease in the adhesive strength of the adhesive layer. Therefore, the adhesive layer can exert sufficient adhesive strength to be attached to the skin. Therefore, it is preferable to use the patch by directly attaching this adhesive layer to the skin. Effect of the Invention
[0064] By employing the above-mentioned configuration, the present invention can provide a patch that reduces deterioration in adhesiveness and improves the transdermal absorbability of a hydrophilic drug. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0065] The present invention will be described in more detail below using examples, but the present invention is not limited thereto. EXAMPLES
[0066] In the examples and comparative examples described below, guanfacine hydrochloride, azelastine hydrochloride, ropinirole hydrochloride, and donepezil hydrochloride were used as hydrophilic drugs.
[0067] Guanfacine hydrochloride has the highest solubility in water having a temperature of 25° C. and a pH of 2 among waters having a temperature of 25° C. and a pH of 2 to 9, and the solubility of guanfacine hydrochloride in water having a temperature of 25° C. and a pH of 2 was 0.16 g or more. The solubility of guanfacine hydrochloride in ethyl acetate and toluene, both having a temperature of 25° C., was 0.040 g or less and 0.039 g or less, respectively.
[0068] Azelastine hydrochloride has the highest solubility in water having a temperature of 25° C. and a pH of 2 among waters having a temperature of 25° C. and a pH of 2 to 9, and the solubility of azelastine hydrochloride in water having a temperature of 25° C. and a pH of 2 was 0.16 g or more. The solubility of azelastine hydrochloride in ethyl acetate and toluene at a temperature of 25° C. was 0.040 g or less and 0.042 g or less, respectively.
[0069] Of water having a temperature of 25° C. and a pH of 2 to 9, ropinirole hydrochloride has the highest solubility in water having a temperature of 25° C. and a pH of 2, and the solubility of ropinirole hydrochloride in water having a temperature of 25° C. and a pH of 2 was 0.15 g or more. The solubility of ropinirole hydrochloride in ethyl acetate and toluene, both having a temperature of 25° C., was 0.037 g or less and 0.038 g or less, respectively.
[0070] Of water having a temperature of 25° C. and a pH of 2 to 9, donepezil hydrochloride has the highest solubility in water having a temperature of 25° C. and a pH of 2, and the solubility of donepezil hydrochloride in water having a temperature of 25° C. and a pH of 2 was 0.16 g or more. The solubility of donepezil hydrochloride in ethyl acetate and toluene, both having a temperature of 25° C., was 0.042 g or less and 0.041 g or less, respectively.
[0071] In the following Examples and Comparative Examples, glycerin and propylene glycol were used as the water-soluble liquid additive. Glycerin and propylene glycol were each able to dissolve at 10% by mass or more in water having a temperature of 25° C. and a pH of 7. Glycerin and propylene glycol were each able to dissolve at 10% by mass or more in water having a temperature of 25° C. and a pH of 7. 5 It was liquid at 1 Pa (1 atm).
[0072] In the following Examples and Comparative Examples, isopropyl myristate was used as a percutaneous absorption enhancer. The concentration of isopropyl myristate that was soluble in water having a temperature of 25° C. and a pH of 7 was 1% by mass or less.
[0073] (Preparation of Acrylic Polymer (A1)) A reaction liquid consisting of monomers containing 40 parts by mass of n-octyl acrylate, 50 parts by mass of ethyl acrylate, and 10 parts by mass of N-vinyl-2-pyrrolidone, and 50 parts by mass of ethyl acetate was supplied to a polymerizer, and the inside of the polymerizer was made into a nitrogen atmosphere at 80° C. Then, the monomers were polymerized while adding a polymerization initiator solution obtained by dissolving 1 part by mass of lauroyl peroxide in 30 parts by mass of ethyl acetate and 20 parts by mass of cyclohexane to the reaction liquid over 24 hours, and after the polymerization was completed, ethyl acetate was further added to the reaction liquid to obtain an acrylic polymer (A1) solution having an acrylic polymer (A1) content of 30% by mass.
[0074] (Examples 1 to 11 and Comparative Examples 1 to 9) The adhesive layer contained guanfacine hydrochloride, azelastine hydrochloride, ropinirole hydrochloride, donepezil hydrochloride, glycerin, propylene glycol, urea, isopropyl myristate, alicyclic saturated hydrocarbon resin (manufactured by Arakawa Chemical Industries, Ltd., product name "Alcon"), liquid paraffin, acrylic polymer (A1), and styrene-isoprene-styrene (SIS) block copolymer (manufactured by Kraton, product name "Kraton Guanfacine hydrochloride, azelastine hydrochloride, ropinirole hydrochloride, donepezil hydrochloride, glycerin, propylene glycol, urea, isopropyl myristate, alicyclic saturated hydrocarbon resin, liquid paraffin, acrylic polymer (A1) solution, and styrene-isoprene-styrene (SIS) block copolymer were blended so that the blend amount of each of the adhesive layer solutions (A1, A2, A3, A4, A5, A6, A7, A8, A9, A10, A11, A12, A13, A14, A15, A16, A17, A18, A19, A20, A21, A22, A23, A24, A25, A30, A31, A32, A33, A34, A35, A36, A37, A38, A49, A41, A42, A43, A44, A45, A46, A47, A48, A49, A51, A52, A53, A54, A55, A56, A57, A58, A59, A60, A61, A62, A63, A64, A65, A65, A66, A67, A67, A68, A69 ...
[0075] Next, a 38 μm thick polyethylene terephthalate film that had been treated with a silicone release agent was prepared as a release liner, and the above adhesive layer solution was applied to the silicone release treated surface of this polyethylene terephthalate film and dried at 60°C for 30 minutes to produce a laminate in which a 70 μm thick adhesive layer was formed on the silicone release treated surface of the polyethylene terephthalate film.
[0076] A 25 μm thick polyethylene terephthalate film was prepared as a support, and one side of this support was placed against the adhesive layer of the laminate, and the adhesive layer of the laminate was laminated and integrated onto the support to produce a patch.
[0077] In addition, in each column of the hydrophilic drug, the acrylic polymer (A1), the water-soluble liquid additive, and the urea in Tables 1 and 2, the content ratio of the hydrophilic drug, the acrylic polymer (A1), the water-soluble liquid additive, and the urea relative to the total amount of the hydrophilic drug, the acrylic polymer (A1), the water-soluble liquid additive, and the urea in the adhesive layer (100 parts by mass) is shown by a numerical value enclosed in parentheses.
[0078] Furthermore, in the column for percutaneous absorption enhancer in Tables 1 and 2, the content ratio of the percutaneous absorption enhancer relative to 100 parts by mass of the acrylic polymer (A1) in the adhesive layer is shown by a numerical value enclosed in parentheses.
[0079] In the patches of the Examples and Comparative Examples, the water content in the adhesive layer was 0.5% by mass or less, and the surfactant content in the adhesive layer was 0% by mass.
[0080] (evaluation) The patches of the Examples and Comparative Examples were evaluated for skin permeation amount and adhesiveness according to the following procedures.
[0081] (Skin permeation amount) Immediately after production, the area of the patch is 3cm 2 A test piece was cut out, and a skin excised from the back of a hairless mouse (male, 8-10 weeks old) was fixed to a Franz diffusion cell kept at 37℃, and the test piece was attached to the upper end of the skin with its adhesive layer. Note that physiological saline adjusted to pH 7.2 was used as a receptor liquid, and the lower end of the skin was immersed in this receptor liquid.
[0082] 24 hours after the test piece was applied to the skin, the receptor fluid under the skin was collected and the drug concentration was measured using HPLC (high performance liquid chromatography). The amount of drug permeation was calculated from the drug concentration and the amount of receptor fluid. The calculated amount of drug permeation was calculated based on the area of the test piece (3 cm 2 ) to obtain the skin permeation amount W2 (mg / cm 2 The calculated skin permeation amount W2 (mg / cm 2 ) are shown in the "24-hour skin permeation amount" column in Table 1.
[0083] In addition, the density of the adhesive layer is set to 1×10 3 mg / cm 2 The density of the adhesive layer and the thickness of the adhesive layer (7 × 10 -3cm), the mass per unit area of the adhesive layer is 7 mg / cm 2 The drug concentration (mass%) in the adhesive layer was calculated from the blending amount of each component contained in the adhesive layer. From the calculated mass per unit area of the adhesive layer and the drug concentration in the adhesive layer, the drug amount W1 (mg / cm) per unit area in the adhesive layer immediately after production was calculated. 2 The drug availability 24 hours after the test piece was applied to the skin was calculated based on the following formula, and the results are shown in the "Availability" column of Table 1. Drug availability (%) = 100 × W2 / W1
[0084] (Applicability) Immediately after production, the area of the patch is 5cm 2 A test specimen was cut out. The release liner was peeled off from the test specimen, and the adhesive surface of the test specimen was visually observed to confirm whether or not the liquid component had bled out onto the adhesive surface. The test specimen was then attached to the shaved back skin of a rabbit (male, 16-18 weeks old) using the adhesive layer. 24 hours after attachment, the test specimen was peeled off from the skin and evaluated according to the following criteria. <Evaluation criteria> "Excellent": The liquid component did not bleed out onto the surface of the adhesive layer, the adhesive layer had excellent adhesive strength, and the patch could be attached to the skin and could be peeled off from the skin without leaving any glue residue. "Good": Although a very small amount of liquid components bled out onto the surface of the adhesive layer, the adhesive layer had high adhesive strength, making it possible to apply the patch to the skin and also allowing the patch to be peeled off from the skin without leaving any glue behind. "Acceptable": Although a small amount of liquid components bled out onto the surface of the adhesive layer, the adhesive layer had sufficient adhesive strength, making it possible to attach the patch to the skin and also allowing the patch to be peeled off from the skin without leaving any glue residue. "Not good": A large amount of liquid components bled out onto the surface of the adhesive layer, causing the adhesive layer to have insufficient adhesive strength, making it impossible to attach the patch to the skin, or leaving a residue of glue when the patch was peeled off from the skin.
[0085] In addition, in the patch of Comparative Example 2, in the above-mentioned evaluation of the adhesiveness, when the patch is peeled off after being applied to the skin, adhesive residue occurs, and the patch cannot be peeled off from the skin. Such a patch cannot be used in practice. Therefore, the patch of Comparative Example 2 was not evaluated for the amount of skin permeation.
[0086] In addition, in the patch of Comparative Example 6, immediately after production, a large amount of glycerin bleeds out as a liquid component in the adhesive layer, and the adhesive strength of the adhesive layer is insufficient, so that the patch could not be attached to the skin in the above-mentioned evaluation of the adhesiveness. Therefore, the skin permeation amount was not evaluated for the patch of Comparative Example 6 either.
[0087] [Table 1]
[0088] [Table 2] [Industrial Applicability]
[0089] According to the present invention, as described above, it is possible to provide a patch that reduces the deterioration of adhesiveness and improves the transdermal absorbability of a hydrophilic drug.
Claims
1. A support and an adhesive layer laminated and integrated on one surface of the support, the adhesive layer contains a hydrophilic drug, an acrylic polymer (A) containing 5% by mass or more of an N-vinyl-2-pyrrolidone component, a water-soluble liquid additive, and urea; The water-soluble liquid additive contains a polyhydric alcohol, The adhesive layer contains the acrylic polymer (A) in an amount of 45 parts by mass or more and 90 parts by mass or less, relative to 100 parts by mass of the total amount of the hydrophilic drug, the acrylic polymer (A) containing 5% by mass or more of the N-vinyl-2-pyrrolidone component, the water-soluble liquid additive, and the urea.
2. 2. The patch according to claim 1, wherein the mass ratio of the water-soluble liquid additive to the hydrophilic drug in the adhesive layer (mass of water-soluble liquid additive / mass of hydrophilic drug) is 0.1 or more and 20 or less.
3. 3. The patch according to claim 1, wherein the mass ratio of urea to the water-soluble liquid additive in the adhesive layer (mass of urea / mass of water-soluble liquid additive) is 0.15 or more and 6 or less.
Citation Information
Patent Citations
Resolvent composition for sparingly soluble medicine
JP1993178763A
Plaster
JP1994247847A
Self-adhesive pack sheet for beauty and medical treatment
JP1996319213A
Topical narcotic for external use
JP1998316590A
Percutaneous patch material containing 2,3-diketopiperazine derivative or its salt
JP1999124332A
